A Myc enhancer cluster regulates normal and leukaemic haematopoietic stem cell hierarchies - Bahr, Carsten; Uslu, Veli Vural; Trumpp, Andreas (Nature, 2018)
The transcription factor Myc is essential for the regulation of haematopoietic stem cells and progenitors and has a critical function in haematopoietic malignancies1. Here we show that an evolutionarily conserved region located 1.7 megabases downstream of the Myc gene that has previously been labelled as a ‘super-enhancer’2 is essential for the regulation of Myc expression levels in both normal haematopoietic and leukaemic stem cell hierarchies in mice and humans. Deletion of this region in mice leads to a complete loss of Myc expression in haematopoietic stem cells and progenitors. This caused an accumulation of differentiation-arrested multipotent progenitors and loss of myeloid and B cells, mimicking the phenotype caused by Mx1-Cre-mediated conditional deletion of the Myc gene in haematopoietic stem cells3. This super-enhancer comprises multiple enhancer modules with selective activity that recruits a compendium of transcription factors, including GFI1b, RUNX1 and MYB. Analysis of mice carrying deletions of individual enhancer modules suggests that specific Myc expression levels throughout most of the haematopoietic hierarchy are controlled by the combinatorial and additive activity of individual enhancer modules, which collectively function as a ‘blood enhancer cluster’ (BENC). We show that BENC is also essential for the maintenance of MLL–AF9-driven leukaemia in mice. Furthermore, a BENC module, which controls Myc expression in mouse haematopoietic stem cells and progenitors, shows increased chromatin accessibility in human acute myeloid leukaemia stem cells compared to blasts. This difference correlates with MYC expression and patient outcome. We propose that clusters of enhancers, such as BENC, form highly combinatorial systems that allow precise control of gene expression across normal cellular hierarchies and which also can be hijacked in malignancies.
Gesehen am 03.03.2020